Optical properties of Zn1-x Al x O:NiO transparent metal oxide composite thin films prepared by sol-gel method - Arif, Bilal; El-Nasser, H. M.; Dere, A.; Al-Ghamdi, Ahmed A.; Bin-Omran, S.; El-Tantawy, Farid; Yakuphanoğlu, Fahrettin (Springer, 2015)
The films of Zn1-x Al (x) O:NiO (AZO; Al/Zn = 1.5 at.%, x = 0.5-2.0) were synthesized on glass substrates by sol-gel method. The morphological properties of the films were studied by atomic force microscopy. The surface morphology of the films is found to depend on the concentration of NiO. The optical band gap, Urbach energy and optical constants such as refractive index, extinction coefficient and real and imaginary parts of the dielectric constant of the films were determined. The refractive index dispersion of the films obeys the single-oscillator model, and the single-oscillator parameters were determined. The optical band gap of ZnO film was found to be 3.76 eV, and the optical band gap of the films increases with NiO doping. The obtained results suggest that Zn1-x Al (x) O:NiO films can be used as optical material in optical communication applications. [GRAPHICS] .
Keywords: AZO film; Nickel oxide; Transparent metal oxide film